The effect of follicular fluid selenium concentration on oocyte maturation in women with polycystic ovary syndrome undergoing in vitro fertilization/Intracytoplasmic sperm injection: A cross-sectional study - Seyedeh Mahsa Poormoosavi; Mohammad Amin Behmanesh; Hossein Najafzadeh Varzi; Shabnam Mansouri; Sima Janati (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: A high level of free radicals and oxidative substances in women with polycystic ovary syndrome (PCOS) can affect the ovaries through oxidative stress. Antioxidants such as selenium, a vital trace element in human health, can improve the prognosis of PCOS by reducing oxidative stress. Objective: This study was performed due to the lack of comprehensive information about selenium concentration in follicular fluid and its effect on the oocyte count and quality in infertile women with PCOS. Materials and Methods: In this cross-sectional study, 78 women with PCOS referred to Umm-al-Banin Infertility Clinic Center, Ganjavian Hospital, Dezful, Iran for in-vitro fertilization from March to November 2019 were enrolled. After ovarian stimulation with the antagonist protocol, the oocytes were retrieved under transvaginal ultrasound in in-vitro fertilization/intracytoplasmic sperm injection cycles, and selenium concentrations were measured in the follicular fluid using an atomic absorption method by spectrophotometer device. Oocyte count and morphology were evaluated using inverted optical microscopy. Results: There were no significant differences between follicular fluid selenium concentrations in terms of the total number of oocytes and immature oocytes in the metaphase I and germinal vesicle stages. However, a significantly reduced number of metaphase II oocytes was observed at selenium levels < 40 μg/dL (p = 0.001). Conclusion: Based on our results, low levels of follicular selenium concentration in infertile women with PCOS can reduce the quality and potency of oocyte maturation.